Maintaining the status quo: Constructing institutional citizenship in U.S. higher education policies - Friedensen, Rachel; Gowen, Garrett (Journal of Praxis in Higher Education, 2024)
Institutional policies and plans play a significant role in the daily life of a college or university. In this paper, we explore the ways that policy texts discursively contribute to constructions of institutional citizenship. Using an example drawn from a policy discourse analysis, we explore how institutions (re)make subjectivities according to the institution’s interests. We describe the differential subjectivities produced by this discourse for historically marginalized and historically centered identities and argue that this difference, perpetuated through official policy and instantiated in different institutional citizen discourses, undermines institutional equity efforts. Ultimately, discourses of institutional citizenship work to maintain inequitable status quos, pointing to the potentially conservative nature of both policy and citizenship.